Muc5ac gastric mucin glycosylation is shaped by FUT2 activity and functionally impacts Helicobacter pylori binding - Magalhães, A (2016)
The gastrointestinal tract is lined by a thick and complex layer of mucus that protects the mucosal epithelium from biochemical and mechanical aggressions. This mucus barrier confers protection against pathogens but also serves as a binding site that supports a sheltered niche of microbial adherence. The carcinogenic bacteria Helicobacter pylori colonize the stomach through binding to host glycans present in the glycocalyx of epithelial cells and extracellular mucus. The secreted MUC5AC mucin is the main component of the gastric mucus layer, and BabA-mediated binding of H. pylori to MUC5AC confers increased risk for overt disease. In this study we unraveled the O-glycosylation profile of Muc5ac from glycoengineered mice models lacking the FUT2 enzyme and therefore mimicking a non-secretor human phenotype. Our results demonstrated that the FUT2 determines the O-glycosylation pattern of Muc5ac, with Fut2 knock-out leading to a marked decrease in a1,2-fucosylated structures and increased expression of the terminal type 1 glycan structure Lewis-a. Importantly, for the first time, we structurally validated the expression of Lewis-a in murine gastric mucosa. Finally, we demonstrated that loss of mucin FUT2-mediated fucosylation impairs gastric mucosal binding of H. pylori BabA adhesin, which is a recognized feature of pathogenicity.